Managing grasslands to optimize soil carbon sequestration - Chabbi, Abad (Burleigh Dodds Series in Agricultural Science, 2023)
In this chapter, we will discuss the effect of different grassland management practices on greenhouse gas (GHG) emissions and soil organic carbon (SOC) sequestration. This includes comparison of grasslands with arable croplands, the role of N fertilization, and grazing strategies. Special emphasis will be given to grasslands in rotation with cropping systems and integration with timber systems to improve sustainable management and SOC sequestration.